Analisis Pengaruh Ekspor dan Impor Terhadap Pertumbuhan Ekonomi di Indonesia (Studi Kasus Tahun 2020-2024) - Mila Salbiyah; Fadila Siti Nuraeni; Kylla Almira Rahma Fadzillah; Sri Yulandasari Lajai Mandam; Perwito Perwito (Indo Publishing, 2026)
Indonesia’s economic growth during the 2020–2024 period experienced significant dynamics due to the impact of the COVID-19 pandemic and global trade uncertainties. International trade, particularly export and import activities, plays a crucial role in influencing economic growth through its contribution to national income. This study aims to analyze the effect of exports and imports on Indonesia’s economic growth during the 2020–2024 period. The theoretical framework is based on economic growth theory and the Heckscher–Ohlin theory of international trade, which emphasizes the importance of net exports in driving Gross Domestic Product (GDP). This research employs a quantitative descriptive approach using secondary data on exports, imports, and economic growth obtained from official publications of Statistics Indonesia (BPS). The analysis examines the trends of export and import performance and their relationship with Indonesia’s economic growth. The results indicate that export and import activities fluctuated throughout the study period due to global economic conditions and trade policy adjustments. Exports contributed to increasing foreign exchange earnings and national output, while imports played a significant role in fulfilling domestic demand for raw materials and capital goods to support production activities. Overall, the study concludes that exports and imports have a strategic role in supporting Indonesia’s economic growth, highlighting the need for balanced and sustainable international trade management.